Preliminary evaluation of the benefits of a participatory regional integrated assessment software. - Holman, Ian P.; Harman, J. (Springer Science Business Media, 2008)
This paper provides a preliminary evaluation of the Regional Impact Simulator—a user-friendly, PC-based tool designed with stakeholders for stakeholders wishing to assess the effects of climate and/or socio-economic change on the important sectors and resources in the UK at a regional scale, in particular, impacts to coastal and river flooding, agriculture, water resources and biodiversity. While integrated assessments are relatively new, simulators that help stakeholders visualize and think about potential changes in the environment or society at a regional scale are very new. An earlier project, RegIS1, was the first local/ regional integrated assessment conducted in the UK. It developed a method for engaging stakeholders in a “stakeholder-led” integrated assessment process. The RegIS2 project developed a simulation tool and followed the same “stakeholder- led” principle in designing and testing the tool. The role of stakeholders in informing the design of the simulator is discussed here, as is a stakeholder evaluation survey on its success in meeting its objectives. We also reflect on the need and desire of stakeholders to have such a tool. And because the Steering Committee – made up of stakeholders – was so invaluable in ensuring the usefulness of research outputs, a series of Steering Committee ‘rules’ is proposed intending to maximise the benefits of this valuable resource. Finally, we outline how our experience with the ‘Regional Impact Simulator’ serves as a test-bed for further studies of stakeholder-led, regional,